BIFURCATION ANALYSIS MATHEMATICAL MODEL FOR THE SPREAD OF EXOGENOUS REINFECTION TUBERCULOSIS - Winanda, Rara Sandhy; Ahmad, Defri; Putri, Sovia Helmi; Putri, Ariana (PATTIMURA UNIVERSITY, 2023)
The spread of tuberculosis can occur in two ways, namely exogenous and endogenous. The spread of tuberculosis exogenously or Exogenous Reinfection of tuberculosis can be observed using a mathematical model. Then an analysis of the mathematical model with a bifurcation approach was carried out. Based on the result, it was found that there was a change in stability properties and the type of equilibrium point in the distribution equation system of exogenous reinfection tuberculosis, where the parameter that occurred bifurcation was , with . When value of is smaller than zero, the system of differential equations of exogenous reinfection tuberculosis shows an unstable with a saddle point type, when the value of is equal to zero the system of differential equations cannot be determined its stability, and when system of differential equations shows asymptotic stability, where there is a change in species. The points are nodes, star nodes, and spirals.